A JUNIOR HIGH SCHOOL STUDENTS’ ERROR: ANALYSIS IN MATHEMATICAL STORY OF CARTESIAN COORDINATES USING POLYA STEPS - Maryanto, Andi; Faizah, Hanim; Sugandi, Eko (Kadikma, 2022)
Solving mathematics word problem is an example of problem solving which is helpful to everyday life, but not all students can easily solve it. Most students have difficulty and errors in solving it. Researchers often find in journal information that students struggle to complete a story. In some cases, it is a matter of mathematically shaped stories in the matter of cartesian coordinates. More than a few students are uneasy to solve mathematics word problem. In fact, many students have not known the concept of cartesian coordinates. The purpose of this study is to describe the type of error and the factors that cause students to make a mistake in solving mathematics word problem especially cartesian coordinates with the correct step of understanding the problem, formulating a plan, carrying out a plan, and examining the answer. It is a qualitative study carried out at public junior high school 2 Sukodono. The data of this study consist of data on written tests and interviews with the group A of VIII-A SMPN 2 Sukodono students. The method of data collection of this research is tests and interviews. The method of data analysis in this study id data reduction, test results analysis, display data, and withdrawal or verification. The subject of this study the three students who the most errors. Studies show made that the flaw of subjects 1, subject 2, and subject 3 lie in the understanding of the problem, formulating a plan, carrying out a plan, and examining answer. According to Polya, the three students had problem at the stage of solving mathematics word problem therefore, the three subjects could not continue the work at the next phase of formulalting a plan, carrying out a plan, and examining answer. The cause of the students’ mistakes is that the students did not understand the concept of the matter’s coordinates. Students didm’t understand the problem well, so they didn’t understand the proper problem settlement planning. In short, the results achieved by the student are inadequate.